2005
DOI: 10.1007/s00125-005-1844-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HLA class II, insulin and CTLA4 gene regions on the development of humoral beta cell autoimmunity

Abstract: Aims/hypothesis: The aim of this study was to explore the contribution of genetic factors to the emergence of beta-cell-specific humoral autoimmunity. Subjects and methods: We analysed the effect of HLA class II, insulin (INS; −23 HphI variant) and cytotoxic T-lymphocyteassociated protein 4 (CTLA4 [+49 and CT60]) genes on the appearance of beta-cell-specific autoantibodies in a large population-based birth cohort recruited in Finland. Infants carrying increased risk HLA DQB1 genotypes were monitored for the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
27
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 49 publications
16
27
0
1
Order By: Relevance
“…There was in fact no difference in the frequency of the highest risk associated (DR3)-DQA1*05-DQB1*02/DRB1*0401-DQB1*0302 genotype. This finding is consistent with previous observations according to which children with (DR4)-DQB1*0302 were shown to test more frequently positive for both IAA and IA-2A and to have higher IAA and IA-2A levels (11,12).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There was in fact no difference in the frequency of the highest risk associated (DR3)-DQA1*05-DQB1*02/DRB1*0401-DQB1*0302 genotype. This finding is consistent with previous observations according to which children with (DR4)-DQB1*0302 were shown to test more frequently positive for both IAA and IA-2A and to have higher IAA and IA-2A levels (11,12).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the class II HLA DRB1*0401-DQB1*0302 haplotype, factors controlling the IA-2-restrictive pathogenesis of T1D might include other genetic loci. In previous studies in prediabetic children, the insulin gene INS -(-23)-HphI polymorphism (12), the cytotoxic T-lymphocyte-associated protein 4 (CTLA4)C49 or CT60 polymorphisms (12), or the Arg620Trp variant in the lymphoid tyrosine phosphatase encoding the PTPN22 gene (27) did not affect the production of IA-2A, but the INS and PTPN22 polymorphisms were observed to be associated with the early appearance of IAA and to contribute to the pathogenesis of T1D by initiating/modifying insulinspecific immunity. Further studies are required to unravel the factors influencing the IA-2-restricted response and the possible pathogenetic mechanism behind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that insulin antibodies were lower in both the class I/III and class III/III genotypes than in the class I/I genotype, and confirmed previous findings [11,12] that carriers of class III alleles inherited a higher tolerance towards endogenous insulin, thus possibly relieving the immunological attack on the beta cells. We also found that class III alleles are associated with higher residual beta cell function and that this putative beta-cell-protective effect of class III alleles seemed to be most evident in the class III/III genotype group who, although only eight patients, also seemed to benefit from a clinically evident improvement in glycaemic control (1.1% in insulin-dose-adjusted HbA 1 c, p=0.04).…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to the inclusion criteria used, resulting in a relatively homogeneous study population, but may also reflect the idea that factors contributing to the initiation of the disease process might be different from those driving the process towards overt disease. However, as previously shown (2,3,6,21,22), several of the factors associated with the initiation of b-cell autoimmunity do contribute to the phenomena associated with the progression rate, such as age at initial seroconversion, the pace of progression towards persistent multipositivity and autoantibody levels. The current study confirmed the prior observations that progression to T1D is related to young age at seroconversion, early progression to multipositivity, higher numbers of detectable autoantibodies and to higher levels of ICA, IAA and IA-2A (1, 2, 3).…”
Section: Discussionmentioning
confidence: 80%